2011
DOI: 10.1063/1.3599425
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a 400 GPa pressure in water using converging strong shock waves

Abstract: Results related to the generation of an extreme state of water with pressure up to (4.3 ± 0.2)·1011 Pa, density up to 4.2 ± 0.1 g/cm3, and temperature up to 2.2 ± 0.1 eV in the vicinity of the implosion axis of a converging strong shock wave are reported. The shock wave was produced by the underwater electrical explosion of a cylindrical Cu wire array. A ∼8 kJ pulse generator with a current amplitude ≤550 kA and rise time of 350 ns was used to explode arrays having varying lengths, radii, and number of wires. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…The strong plasma shockwave front rises faster in water, whose duration is around 10 ns, and its pulse falls whose duration is around 100 ns more slowly than it rises. Ice X can be formed when the shockwave front rises, the temperature is around 900 K and the pressure is around 65 Gpa192324, which corresponding with the experimental result point 1 in Fig. 2.…”
Section: Discussionsupporting
confidence: 76%
“…The strong plasma shockwave front rises faster in water, whose duration is around 10 ns, and its pulse falls whose duration is around 100 ns more slowly than it rises. Ice X can be formed when the shockwave front rises, the temperature is around 900 K and the pressure is around 65 Gpa192324, which corresponding with the experimental result point 1 in Fig. 2.…”
Section: Discussionsupporting
confidence: 76%
“…16 This allows this approach for generating converging strong SW by underwater electrical explosion of either cylindrical of spherical wire arrays to be applied in order to obtain an extreme state of water in the vicinity of the SW implosion. 17,18 In the case of a cylindrical wire array explosion, shadow imaging of the generated SW and water light emission in the vicinity of the convergence axis were used to calculate the time-of-flight (TOF) of the SW. 19,20 These data and the $12% efficiency of the stored energy transfer to the converging water flow were used as validation parameters for comparison with the results of one dimension hydrodynamic (HD) simulations, coupled with the experimentally measured energy deposited into the wires and the EOS for water. 21 The results of these simulations showed that in the vicinity of the convergence axis, the values of pressure P % 4.7 Â 10 11 Pa, temperature T % 3 eV, and density q % 4 g/ cm 3 can be reached.…”
mentioning
confidence: 99%
“…Second, the plasma nanobubble begins to collapse and produces electron jets and a shock wave that induce water compression whose duration is about 5 ns. 36 The shock wave front rises faster in water, and its pulse falls more slowly than it rises. Ice-VII can be formed when the shock wave front rises, the temperature is around 900 K, and the pressure is around 20 GPa, 36,37 but the lifetime of ice-VII is so short that it cannot exist when the descending edge of the laser pulse reaches the region of "compressed-state water."…”
Section: Resultsmentioning
confidence: 99%
“…The water pressure declines slowly and uniformly. 38 The shock wave generates approximately 10 GPa pressure and 270 K temperature 32,36,39,40 when the shock wave pulse falls. Under these conditions, ice-VIII can be obtained.…”
Section: Resultsmentioning
confidence: 99%